Recruitment, Compensation, and Leadership on Employee Performance with The Supervision of PT Garuda Indonesia's Work - Fadhila, Ghea Ajrina; Yuniawan, Ahyar (Management Analysis Journal, 2021)
The reason of this think about is to decide the influence of a few factors counting Competency, Remuneration, and Authority on Worker Execution. The question of this think about is a permanent employee of PT. Garuda Indonesia Jakarta. The methods used are Descriptive and Simple Regression Methods are used to test hypotheses. Respondents included in this consider as many as 108 employees. This study used saturated sampling method and data collection was conducted using questionnaires. The results showed that Recruitment partially has an affect on Performance, Compensation partially has an affect on Performance, and Leadership partially has an affect on employee performance.